Facilitating Perinatal Access to Resources and Support (PeARS): a feasibility study with external pilot of a novel intervention - Pauline Slade; Melanie Dembinsky; Katie Bristow; Kim Garthwaite; Amy Mahdi; Annette James; Atif Rahman; Soo Downe (BMC, 2021)
Abstract Background Up to 50% of women in areas of high socio-economic deprivation are at risk of developing depressive symptoms in pregnancy. Feeling well supported, can facilitate good mental health perinatally. A brief, innovative intervention to facilitate access to support and resources was developed and tested. This included one antenatal and one postnatal session, each with three evidence-based components: i) support from a non-professional peer to enable a woman to identify her needs; ii) information about local community services and signposting; and iii) development of a personalised If-Then plan to access that support. The aims were to evaluate the intervention and research methods for feasibility and acceptability for perinatal women, maternity care providers and peers, and provide preliminary effectiveness indications. Methods Pregnant women living in an area of high deprivation were recruited from community-based antenatal clinics and randomised to intervention or control condition (a booklet about local resources). Outcome measures included women's use of community services by 34 + weeks gestation and 6 months postnatally; mental health and wellbeing measures, and plan implementation. Interviews and focus groups were conducted with women participants, providers, and peers. Data were analysed using framework analysis. Recruitment and retention of peers and participants, intervention fidelity, and acceptability of outcome measures were recorded. Results Peer facilitators could be recruited, trained, retained and provide the intervention with fidelity. One hundred twenty six women were recruited and randomised, 85% lived in the 1% most deprived UK areas. Recruitment constituted 39% of those eligible, improving to 54% after midwifery liaison. Sixty five percent were retained at 6 months postnatally. Women welcomed the intervention, and found it helpful to plan access to community services. Providers strongly supported the intervention philosophy and integrated this easily into services. The study was not powered to detect significant group differences but there were positive trends in community service use, particularly postnatally. No differences were evident in mental health and wellbeing. Conclusions This intervention was well received and easily integrated into existing services. Women living in highly deprived areas could be recruited, randomised and retained. Measures were acceptable. Peer facilitators were successfully trained and retained. Full effectiveness studies are warranted.